Gestures (Emblems) in the Preliminary Translational Analysis of a Literary Text - Curkan-Dróżka, Ełona (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2024)
This paper deals with the interpretation of the elements of non-verbal communication in the process of translation-oriented text analysis. The discussion focuses on the reasons why these el¬ements are often omitted during the analysis of literary texts by novice researchers. The author invokes issues related to the perception of the components of non-verbal communication, citing sources from the fields of anthropology, literature, and culture and focusing on the perception of gestures, their role in the creation of literary characters as well as their close connection to the cul¬ture of the source text. Attention is paid to the perpetuation in literature of certain norms of social behavior in a given historical period and to the influence of authorial creation on the characteristic features of non-verbal communication of individual characters. Thus, non-verbal communication behavior is shown to be a rich source of information, significantly deepening not only the portrayal of characters, but also the depiction of the realities of everyday life. In order to properly interpret non-verbal sources of information such as visuals, their origin, and semantics, the translator should pay due attention to them during the analysis of the literary text. Emblems are distinguished by their greatest cultural significance among the other gesture types. The author describes the most important functions of gestures in the text and their significance for the socio-psychological portrait of characters.